Carbon Sequestration Potential in Aboveground Biomass of Hybrid Eucalyptus Plantation Forest - Siti Latifah; Nurdin Sulistiyono (Jurnal Manajemen Hutan Tropika, 2013)
Forests are a significant part of the global carbon cycle. Forests sequester carbon by conducting photosynthesis, which is the process of converting light energy to chemical energy and storing it in the chemical bonds of sugar. Carbon sequestration through forestry has the potential to play a significant role in ameliorating global environmental problems such as atmospheric accumulation of GHG's and climate change. The present investigation was carried out to determine carbon sequestration potential of hybrid Eucalyptus. This study was conducted primarily to develop a prediction model of carbon storage capacity for plantation forest of hybrid Eucalyptus in Aek Nauli, Simalungun District, North Sumatera. Models were tested and assessed for statistical validity and accuracy in predicting biomass and carbon, based on determination coefficient (R) and correlation coefficient (r), aggregative deviation percentage (AgD), and the average deviation percentage (AvD). The best general model to estimate the biomass of hybrid Eucalyptus was Y = 1351,09x^0,876. e^(0,094). Results showed that hybrid Eucalyptus had an average above-ground biomass in year 0 (the land without the eucalyptus trees) up to year 3 as large as 1.36, 11.56, 43.18, and 63.84 t ha. The carbon content of hybrid Eucalyptus were 0.61, 5.2, 19.43 t^(-1), and 28,73 t^(-1) C ha while the carbon sequestration potential were 2.23, 19.08, 71.31, and 105.43 t^(-1) CO ha^(-1) respectively.